Alterations in small RNA profiles in liver following a subchronic exposure to a low-dose pesticide mixture in Sprague-Dawley rats. (15th December 2021) - Mesnage, Robin; Mahmud, Nadiya; Mein, Charles A.; Antoniou, Michael N.
Highlights: Small RNAs are biomarker to monitor health and track the development of diseases. We report changes in small RNAs in the liver of rats exposed to a pesticide mixture. 9 miRNAs with known health roles were altered by the pesticide mixture treatment. High- throughput 'omics' analyses are sensitive and accurate markers of health risks. Abstract: Small RNAs have emerged as a promising new type of biomarker to monitor health status and track the development of diseases. Here we report changes in the levels of small RNAs in the liver of rats exposed to a mixture of six pesticides frequently detected in foodstuffs (azoxystrobin, boscalid, chlorpyrifos, glyphosate, imidacloprid and thiabendazole). Multivariate analysis with OPLS-DA methods showed that small RNA profiles can discriminate samples from pesticide treated rats from their concurrent controls. A total of 9 miRNAs were found to have their levels altered in the liver of the pesticide-treated rats in comparison to the controls, which included 7 that were downregulated (miR-22-5p, miR-193a-3p, miR-32-5p, miR-33-5p, miR-122-5p, miR-22-3p, miR-130a-3p) and 2 that were upregulated (miR-486-5p, miR-146a-5p). These miRNAs were predicted to regulate genes, which were found to have their expression altered by the pesticide mixture and have known health implications in the regulation of hepatic metabolism. This supports and extends our recent conclusions that high- throughput 'omics' analyses can reveal molecular perturbations, which can potentially act as sensitive and accurate markers of health risks arising from exposure to environmental pollutants such as pesticides.